Understanding Sustainability and FAIRness of Research Software - Feitosa, Daniela; von Flach, Christina; Costa, Joenio (Anais do Workshop de Práticas de Ciência Aberta para Engenharia de Software (OpenScienSE), 2023)
The increasing use of research software has urged the scientific community to discuss its sustainability, FAIRness, and ability to support the reproduction of studies by independent researchers. In this paper, we present the results of an exploratory study conducted with a research group in Applied Physics, whose researchers historically developed most of their research software. We analyzed the sustainability and FAIRness of one research software developed by the group and reported the results. Our study allowed us to broaden our understanding of evaluating sustainability and FAIRness, and related challenges, to support future evaluations of research software.